2020
DOI: 10.1142/s242478632050005x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of audit committee attributes on financial distress: Evidence from Pakistan

Abstract: This research study compares the financially distressed and financially healthy companies, based on their audit committee attributes over the 2006–2010 period. While focusing on the manufacturing sector of Pakistan, the logit regression results reveal that audit committee composition and audit committee opinion have significant impact on the financial distress of the companies while audit committee size has insignificant impact on financial distress. The first of its kind, this study, benefits investors, finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
3
6
0
5
Order By: Relevance
“…Coinciding with Rahmat et al (2009) and Khalid et al (2020), this research finds out that there is no significant relationship between SMEs’ financial distress and AUDSIZE. Hence, the agency theory is not supported by result since it requires small audit committee to fulfill their monitoring rules for firms to avoid financial distress.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Coinciding with Rahmat et al (2009) and Khalid et al (2020), this research finds out that there is no significant relationship between SMEs’ financial distress and AUDSIZE. Hence, the agency theory is not supported by result since it requires small audit committee to fulfill their monitoring rules for firms to avoid financial distress.…”
Section: Resultssupporting
confidence: 72%
“…Empirically, Rahmat et al (2009) and Khalid et al (2020) find that there is no significant relationship between SMEs' financial distress and audit committee size. 2.2.2.3.3.…”
Section: 22mentioning
confidence: 99%
“…Many studies have been conducted in the local context to examine the impact of effective governance mechanisms on the likelihood of FD and have concluded that an efficient governance structure not only improves a firm financial performance but also protects it from FD (Jamal and Shah, 2017;Taj et al, 2017;Udin et al, 2017;Khurshid et al, 2018;Khalid et al, 2020;Farooq et al, 2020). Management is expected to use CSR activities to align the interests of various stakeholder groups in an effective governance structure, thereby indirectly protecting the firm from distress.…”
Section: Corporate Social Responsibility Financial Distress and Corpo...mentioning
confidence: 99%
“…Variabel ini digunakan untuk mengontrol pengaruh ukuran perusahaan terhadap variabel yang diteliti. Variabel ini diukur dengan me-log-kan total asset (Khalid et al, 2020). Leverage adalah variabel yang menunjukkan seberapa besar komposisi utang yang dimiliki perusahaan.…”
Section: Definisi Dan Pengukuran Variabel Real Earning Managementunclassified
“…leverage merupakan variabel kontrol yang digunakan untuk mengontrol pengaruh besaran liabilitas perusahaan terhadap variabel yang diteliti. Variabel ini diukur dengan membagi total hutang dengan total asset (Khalid et al, 2020)…”
Section: Definisi Dan Pengukuran Variabel Real Earning Managementunclassified